THE ESL TEACHERS’ WILLINGNESS TO COMMUNICATE IN ENGLISH - Lo, Yueh Yea (Universitas Pendidikan Indonesia, 2018)
Willingness to communicate (WTC) as introduced by McCroskey and Bear (1985) has developed and been perceived by many as a critical field. Unfortunately, there is a noticeable gap in research on the willingness to communicate (WTC) in English among ESL teachers in the Malaysian context. This study aims to investigate the ESL teachers’ willingness to communicate in English in terms of gender and school locations. The four constructs of communication in WTC are group discussions, interpersonal, public, and talking in meetings. Through both criterion and convenience sampling, 250 ESL teachers from twenty-five schools were chosen for this research. Survey questionnaire with a total of 20 items adopted from McCroskey (1992) was used as the data collection instrument. Findings reveal that ESL teachers' willingness to communicate in English is generally high and that the teachers were more willing to converse and exchange ideas orally in English during the meeting rather than in group or public. Female participants were significantly different in their overall willingness to communicate as they were more willing to communicate in groups and public. The within-group comparison also shows that school locations (urban and rural) affect ESL teachers' willingness to communicate in English. The findings also suggest that schools should encourage more ESL teachers to participate in activities such as debates, drama, public speaking, English language clubs/society, and empower them by providing professional development workshops or training.